Formation of pH-responsive polymer composite membranes by plasma-induced graft polymerization method - Kravets, Liubov; Dinescu, Gheorghe; Dmitriev, Sergey (International Conference on Plasma Surface Engineering, 2013)
The structure and the transport properties of polymer composite membranes consisting of a porous substrate and a polymer layer obtained by plasma-induced graft polymerization method were studied. It has shown that the presence of the polymer layer on the surface of porous substrate leads to changing its transport properties - the water permeability of the formed composite membranes substantially depends on the solution pH. These changes are caused by convertible conformational transitions of macromolecules of the grafted polymer layer from an expanded state into a compact one which is in turn caused by the degree of ionization of the functional groups on the surface of this layer.